Regeneration of Invitro Plantlets in Hemidesmus indicus (L.) R. Br. through Nodal and Leaf Explants - Thirumal Sivakumar, Arumugam Krishnan Shanmugapriya* (International Multidisciplinary Research Journal, 2012)
Invitro plantlet regeneration of Hemidesmus indicus (L.) R.Br, through nodal and leaf explants were attempted by culturing on MS medium supplemented with various PGRs. Nodal and leaf explants induced callus on media containing 2,4-D, 2,4,5-T, 2ip, IAA, NAA, BAP and KIN. The highest frequency of callus was observed in the leaf explants supplemented with 1.0, 3.0, 5.0 mgL-1 concentration of IAA, NAA, IBA. Rhizogenesis was observed in leaf explants highly in Auxin treatment like 2,4-D and 2,4,5-T with the concentrations of 0.2 mgL-1 and 0.5 mgL-1 respectively. Shoot differentiation was obtained from the callus of nodal explants on MS-medium with 1.0, 3.0, 5.0 mgL-1 of 2,4,5-T, KIN and BAP. Regenerated shoots showed rhizogenesis in MS-medium supplemented with 0.5 mgL-1 of IBA and KIN. Eight week old rooted invitro plantlets of H.indicus were removed from the culture vessels and transplanted into plastic pots. The plantlets were exposed to a relative humidity of 80%-90% and temperature 28±2ºC during day time, and 24 ±2ºC during night time. The percentage of surviving plantlets were recorded after four weeks of acclimatization. More than 95% of acclimatized plantlets grew vigorously without any morphological abnormalities.